If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(2x + -8) = 77x Reorder the terms: 7(-8 + 2x) = 77x (-8 * 7 + 2x * 7) = 77x (-56 + 14x) = 77x Solving -56 + 14x = 77x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-77x' to each side of the equation. -56 + 14x + -77x = 77x + -77x Combine like terms: 14x + -77x = -63x -56 + -63x = 77x + -77x Combine like terms: 77x + -77x = 0 -56 + -63x = 0 Add '56' to each side of the equation. -56 + 56 + -63x = 0 + 56 Combine like terms: -56 + 56 = 0 0 + -63x = 0 + 56 -63x = 0 + 56 Combine like terms: 0 + 56 = 56 -63x = 56 Divide each side by '-63'. x = -0.8888888889 Simplifying x = -0.8888888889
| 4a-6(4-2a)=68 | | 32+f=40 | | y+2=2 | | -32=-8(1-3x) | | 3n+9+n=-2.3 | | .50x+.25(30)=47.5 | | 8g+18=-62 | | [4m+1]+3=24 | | 136=-107 | | -(3y+4)-(-2y-6)=2 | | 3559-45(456)+37=567x+55x | | w^2+28w+52=0 | | 2x-54=x+21 | | 23-7(x+3)+5=10 | | d-257*8=8328 | | 5d+3=28 | | 3x^2-5x=3x^2+6 | | 6n-3(4n+4)=30 | | 2x+4x=15 | | 4m+8m=96 | | 67.984-90.9=77x-3x+55.23 | | 9(4x+-5)=3(12x+7) | | 7+6r-6=8r+9-6r | | -8(-8+2r)=-24-5r | | 85*5.009+3.98=66x | | 278=212-u | | 12x=6-3x | | 98+66.7=55.98x+44 | | (x)(x+4)=91 | | 8m+10m=144 | | 4x-9+3x+6-x-4= | | 43.98+33x=96.8*4 |